Knockdown of α-Enolase (ENO1) to Suppress Glycolytic Pathway in Human Hepatocellular Carcinoma Cell Line (HepG2) - AL-Asady, Shaymaa Hamed; AL-Sudani, Basma Talib; Mshimesh, Bahir Abdul-Razzaq (Iraqi Journal of Pharmaceutical Sciences, 2024)
ABSTRACT Hepatocellular carcinoma therapies which are potentially curative depend on early diagnosis, but unfortunately only 20% is the 5-year survival rate of liver cancer despite of various treatment methods which progress continuously. Patients with hepatocellular carcinoma presenting with late stage disease despite established screening guidelines for patients at risk because of asymptomatic nature of this disease so finding effective treatments are imperative. Alpha-enolase has been noticed to be commonly over-expressed in tumors including hepatocellular carcinoma, it is one of the leading regulators of the Warburg effect, so plays an important role in carcinogenesis and tumor maintenance. In this study the cell line α-enolase short interference RNA was successfully constructed. In the α-enolase short interference RNA cell lines, messenger RNA and protein expression of α-enolase were lower than those in negative control and blank control groups. The pyruvate level was significantly inhibited, the proliferation ability was significantly suppressed. Our data provide strong evidence that α-enolase short interference RNA can efficiently suppress glycolysis pathway and thus the proliferation of Hep G2, which may provide a novel gene therapy for hepatocellular carcinoma.